2008
DOI: 10.1095/biolreprod.107.064196
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Transcription Factor, BHLHB8, Involved in Mouse Seminal Vesicle Epithelium Differentiation and Function1

Abstract: The seminal vesicle is a male accessory sex organ that develops from segments of the Wolffian duct adjacent to the urogenital sinus. It produces most of the seminal plasma in both humans and rodents. To date, very few transcription factors have been linked to the development and differentiation of seminal vesicles. In this study, we have examined the role of basic helix-loop-helix (BHLH) B8 transcription factor expressed at high levels in the adult seminal vesicle and during seminal gland differentiation. Immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 58 publications
(89 reference statements)
0
5
0
Order By: Relevance
“…The results from this study suggest that mutations in MIST1 could also be linked to the disease. A complete absence of MIST1 is not deleterious to overall health, reproductive ability, viability, and survival of the mice [17], [33] indicating that altered MIST1 function can go unnoticed for long periods of time. While a small percentage of Mist1 −/− mice do develop more overt fibrosis and inflammation characteristic of chronic pancreatitis, the majority (95%) of the mice are relatively unaffected.…”
Section: Discussionmentioning
confidence: 98%
“…The results from this study suggest that mutations in MIST1 could also be linked to the disease. A complete absence of MIST1 is not deleterious to overall health, reproductive ability, viability, and survival of the mice [17], [33] indicating that altered MIST1 function can go unnoticed for long periods of time. While a small percentage of Mist1 −/− mice do develop more overt fibrosis and inflammation characteristic of chronic pancreatitis, the majority (95%) of the mice are relatively unaffected.…”
Section: Discussionmentioning
confidence: 98%
“…At grade 6, at which point sperm analysis using ejaculated semen collected by electroejaculation stimulation was possible, development of the epithelial cell layer including glandular secretions was noted in the seminal vesicle. These secretions produce most of the seminal fluid that affects sperm capacitation and motility, and toxicity on the fluid or fluid production may have an effect on male fertility (Pin et al 2008; Coroner et al 1992; de Lamirande et al 2001; Huang, Chu, and Chen 2000; Kawano and Yoshida 2007). Therefore, considering the notable development of the epithelial layer in the prostate and seminal vesicle from grade 5 and through grade 6, as well as that of the accessory reproductive organs, thorough evaluation of male reproductive toxicity was considered feasible at grade 6.…”
Section: Discussionmentioning
confidence: 99%
“…In mice, most of the branching in the seminal vesicle is complete at approximately 2 weeks after birth, and at this stage, epithelial cell differentiation begins and cells assume a highly secretory function. Through hypertrophy, the gland continues to grow into adulthood (Pin et al 2008). Brewster (1985) reported that in humans, at 18 years of age, seminal vesicles showed extensive epithelial folding around the circumference of the lumen, and at 45 years of age, there was a great increase in the extent of the epithelial folding in the seminal vesicle when compared with that in the specimen from the 18-year-old.…”
Section: Discussionmentioning
confidence: 99%
“…The Drosophila homolog for MIST1 is dimmed (6) and the gene nomenclature in mice has recently changed from Bhlhb8 (17) to Bhlha15. MIST1 is expressed in serous exocrine cells including acinar cells in the pancreas (16).…”
Section: General Functionmentioning
confidence: 99%
“…An absence of MIST1 also affects the differentiation and/or morphology of other serous exocrine cells include salivary glands (9), gastric epithelium (9,20), mammary gland alveolar cells (25), seminal vesicle (17), and plasma cells (2, 3).…”
Section: Mist1 In Pancreasmentioning
confidence: 99%